PENGARUH AKRUAL, ARUS KAS OPERASI, UKURAN PERUSAHAAN, DAN TINGKAT HUTANG TERHADAP PERSISTENSI LABA - Iis Fitriani, 13.05.52.0203; Indarti, MG. Kentris (Students Journal of Accounting and Banking, 2017)
This study examines the effect of accrual, operating cash flow, firm size, andthe level of debt to earnings persistence. This reseach was conducted at the Indonesian Stock Exchange periode of 2013 through 2015. Unit manufacturing companies that have gone public. The sampling method using purposive sampling the study period of 2013 through 2015. The analysis technique that used is multiple regression analysis using SPSS 23. As a condition for statistical testing has been done normality test and classical assumption that the result show that distribution is the norm and escaped from the classical assumption. The result showed that accrual and operating cash flow does not effect on earnings persistence. firm sizepositive effect on earnings persistence. The level of debt negative effect on earnings persistence.Keywords: Accrual, Operating Cash Flow, Firm Size, The Level of Debt, and Earnings Persistence